Climate Action Plans Under Climate-Resilient Urban Policies - Yilmaz, Dilara; Işinkaralar, Öznur (Kastamonu Üniversitesi, 2021)
Climate change, which is among the biggest environmental problems of today, affects the lives of all living things economically, socially, and environmentally, both in the city and on a global scale. Especially in the climate change process, which has inevitable effects on urban systems and population, action plans come to the fore within the framework of the concepts of climate resilience and vulnerability. Thanks to these plans, mitigation and adaptation policies are produced against negative situations that arise or are predicted to occur in cities. The effects of climate change on each city are different. In this context, it is an important requirement for urban actors to determine their degree of combating the effects of climate change and their adaptation capacities in cooperation.This study, it was aimed to evaluate successful climate action plans in the world and in Turkey in the process of combating climate change. In this context, first of all, successful climate action plans were determined and examined by literature review. Then, common policies and strategies were determined and suggestions were developed to prepare the ground for the climate change struggle processes of other cities.

Günümüzün en büyük çevre sorunları arasında olan iklim değişikliği hem kent hem de küresel ölçekte ekonomik, sosyal ve çevresel açıdan bütün canlıların yaşamlarını etkilemektedir. Özellikle kentsel sistemler ve nüfus üzerinde kaçınılmaz etkileri olan iklim değişikliği sürecinde, iklime dirençlilik ve kırılganlık kavramları çerçevesinde eylem planları ön plana çıkmaktadır. Bu planlar sayesinde, kentlerde ortaya çıkan veya çıkması öngörülen olumsuz durumlara karşı azaltım ve uyum politikaları üretilmektedir. İklim değişikliğinin her kent üzerinde etkileri farklı olmaktadır. Bu kapsamda kentsel aktörlerin işbirliği içerisinde iklim değişikliğinin etkileri ile mücadele edebilme derecelerini ve uyum kapasitelerini belirlemeleri önemli bir gerekliliktir. Yapılan bu çalışmada iklim değişikliği ile mücadele sürecinde Dünya’da ve Türkiye’de başarılı iklim eylem planlarını değerlendirmek amaçlanmıştır. Bu bağlamda, ilk olarak literatür taraması yapılarak başarılı iklim eylem planları tespit edilmiş ve irdelenmiştir. Ardından ortak politikalar ve stratejiler belirlenerek diğer kentlerin iklim değişikliği mücadele süreçlerine zemin hazırlamak amacıyla öneriler geliştirilmiştir.
Keywords: Engineering; climate change; climate resilience; climate action plans; mitigation; adaptation; Mühendislik; 13. Climate action; 11. Sustainability; 12. Responsible consumption